The role of higher education policy in planning information governance at UIN Maulana Malik Ibrahim - Nita Siti Mudawamah; Annisa Fajriyah; Ganis Chandra Puspitadewi; Firman Jati Pamungkas; Aulia Mi'rojtin Firdaus (Perpustakaan Universitas Gadjah Mada, 2024)
Introduction. This study aims to explore the role of higher education policy in planning information governance at the Islamic university, UIN Maulana Malik Ibrahim. Data Collection Methods. The datacollection technique involved was depth interviews with LPM expert staff, the head of the general division of the faculty, public relations, and an archivist. In addition, to conduct the interviews, reference materials were collected to compile previous studies. Data Analysis. The data analysis technique encompassed data reduction, data presentation, and conclusion drawing and verification. Results and Discussion. There is an important role of higher education policy in the process of information management at UIN Maulana Malik Ibrahim. This formulation refers to principles of information governance, which include definition of each party's role, the development of policies and implementation strategies in the governance process, monitoring and auditing of processes and stages of the governance process, information organization processes, and classification. Information, stakeholder participation, and the long-term viability of information governance processes are all important considerations. Conclusion. Information governance should conducted by the policies established by the relevant educational institution. If the information creation, processing, and governance divisions work properly, locating and acquiring information for institutional reasons should be a breeze.